Identification of substituted benzothiazole sulfones as potent and selective inhibitors of endothelial lipase. Issue 15 (1st August 2019) - Kim, Soong-Hoon; Johnson, James A.; Jiang, Ji; Parkhurst, Brandon; Phillips, Monique; Pi, Zulan; Qiao, Jennifer X.; Tora, George; Ye Chen, Alice; Liu, Eddie; Yin, Xiaohong; Yang, Richard; et al.
Graphical abstract: Abstract: A low level of high density lipoprotein (HDL) is an independent risk factor for cardiovascular disease. HDL reduces inflammation and plays a central role in reverse cholesterol transport, where cholesterol is removed from peripheral tissues and atherosclerotic plaque. One approach to increase plasma HDL is through inhibition of endothelial lipase (EL). EL hydrolyzes phospholipids in HDL resulting in reduction of plasma HDL. A series of benzothiazole sulfone amides was optimized for EL inhibition potency, lipase selectivity and improved pharmacokinetic profile leading to the identification of Compound 32 . Compound 32 was evaluated in a mouse pharmacodynamic model and found to show no effect on HDL cholesterol level despite achieving targeted plasma exposure (Ctrough > 15 fold over mouse plasma EL IC50 over 4 days).